Edwin Eells letter, - Eells, Edwin, 1841-1917
One letter from Edwin Eells to Caroline Hathaway of Spokane Public Library. Eells is responding to a letter with a newspaper clipping asking about his father, Cushing Eells. In the letter, he disputes some statements by a Mr. Edwards, and a story of "lost Indian." He disputes other facts from the article concerning his father's life.